PERAN GURU DALAM MEMBENTUK KECERDASAN EMOSIONAL SISWA KELAS III MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Nisa Nadia Madani; Dadan Mardani; Dewi Utami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Teachers play a crucial role in developing students' emotional intelligence at school, serving not only as teachers but also as determinants of the quality of education. This study is motivated by the importance of emotional intelligence that affects students' social interactions, character development and mental well-being. Observation in grade III shows that students tend to be explorative and active in seeking new experiences. As the highest level of primary education, grade III students often feel more mature and play the role of older siblings. Students with stable emotional intelligence are usually obedient and able to distinguish the right actions, while students with less stable emotions face difficulties in controlling their emotions. This research aims to find out 1) the role of teachers in shaping the emotional intelligence of third grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun, 2) supporting and inhibiting factors in shaping emotional intelligence of third grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. The method used was descriptive qualitative approach. Data collection techniques used were observation, interview, and documentation. This research obtained the following results: 1) The role of teachers in shaping students' emotional intelligence in class III of Madrasah Ibtidaiyah Ma'had Al-Zaytun is teacher as educator, teacher as motivator, teacher as facilitator, teacher as mediator, teacher as guide, teacher as director, and teacher as parent. 2) Supporting factors in fostering students' emotional intelligence are conducive environment, social caring attitude and habituation of saying please, sorry and thank you. The inhibiting factors in fostering students' emotional intelligence are the lack of communication between parents and teachers, feelings of homesickness, social background, family economic background and teacher psychology in the process of guiding students. Keywords: Teacher's Role, Emotional Intelligence, Madrasah